Preparation and Certification of a Reference Material in Ultra Pure Water Density - Chavarría Sánchez, Jessica (2014)
Conductivity and total hardness in ultrapure water samples produced by four combinations of purification water equipment were studied. Production of reference material method chose the group of purification equipment which allow obtaining water samples with minor conductivity and total hardness. Several processes for the certification of the material were performed as well: study of conductivity versus time, study of the effect of filling and package processes, density value assignment, four different temperatures, using variable methods and stability studies in the magnitudes of conductivity and density. Finally results of the certification were reported in the certificate for the certified reference material in density of ultra-pure water batch.